A systematic review and meta-analysis on association between social non-participation and falling in depressive state among the older adult people - Priya Das; Subhadeep Saha; Tanu Das; Partha Das; Ranjan Roy; Tamal Basu Roy (Discover Mental Health)
Abstract Geriatric depression is one of the most common mental disorders globally. The relationship between social participation and having depressive disorders can be considered as reciprocal. The main aim of this present study was systemizing the evidences on the influence of social non-participation on depression among older adults. Systematic review specifically Meta-analysis was performed to show the adverse impact of social non-participation on depression among the older adults. Maintaining all the inclusion and exclusion criteria required for this systematic review, empirical studies conducted within the last decade only investigating the association between social non-participation and depression were retrieved and summarized. Database searches were performed in Scopus, PubMed, Medline, Google scholar, Web of Science, SocINDEX, PsycINFO and ProQuest platforms. A total number of 10 studies were added to conduct meta-analysis. Majority of the studies (6) examined that the older people who did not participate socially had more likelihood of getting depressed. The average effect size across all studies using random effects model was found as OR-2.07 [95% CI: 1.49–2.65] which suggested that the older people having no social participation were 2.07 times more likely of becoming depressed than those participated in social events. As with increasing ages, different health issue arises and social isolation increases; effective social gerontological interventions are required for achieving better mental health of older people. Future research should include long-term follow up and repeated measures to longitudinally investigate the effect of social participation on geriatric depression.